1995
DOI: 10.1111/j.1365-2621.1995.tb05671.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Anthocyanins in Callus Cultures of Cranberry (Vaccinium macrocarpon Ait)

Abstract: Expression of anthocyanins and other flavonoids in callus cultures established from different parts of cranberry plant was investigated and the effect of explant source on the in vitro product was determined. Callus cultures were initiated from different parts of the plant in a modified Gamborg's medium with 5.37 pM o-naphthaleneacetic acid, 0.45 pM 2,4-dichlorophenoxyacetic acid, and 2.32 pM kinetin in the dark at 25°C. Callus cultures accumulated anthocyanins only on exposure to light and maximum concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 36 publications
(38 reference statements)
0
12
0
1
Order By: Relevance
“…and Vaccinium phalae (ohelo) (Madhavi et al, 1995;Fang et al, 1999). This allowed the subsequent development of suspension culture to produce anthocianins.…”
Section: Callus Induction and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…and Vaccinium phalae (ohelo) (Madhavi et al, 1995;Fang et al, 1999). This allowed the subsequent development of suspension culture to produce anthocianins.…”
Section: Callus Induction and Growthmentioning
confidence: 99%
“…Some authors have explained that this phenomenon may be due to the attribution of abiotic or biotic stress factors from the surrounding environment, time of harvesting, climatic conditions, geographic origin, plant development and even crop type (organic, wild or agricultural) (Vitrac et al, 2002;Li et al, 2006). The comparative studies between in vivo and in vitro material (calli) to quantify secondary metabolites have been conducted for species like Vaccinium macrosporum and Buddleja cordata (Madhavi et al, 1995;Estrada-Zuniga et al, 2009). Presently, however, very few successful examples of the commercial application of cellular suspensions exist due to the low biosynthesis of the compound, differentiation and compartmentalization of cells, lack of developing organelles, unstable cellular lines and the difficulty of scaling production (Kolewe et al, 2008;Estrada-Zuniga et al, 2009).…”
Section: Quantification Of T-r and T-p In Plant Materialsmentioning
confidence: 99%
“…HAMAMATSU et al Peak No. (a) tR ( was reported for cranberry (V macrocarpon Ait) callus derived from leaf, stem and fruit, whereas fruit produced Pn 3-gal, Cy 3-gal, Cy 3-ara, Pn 3-ara and Pn 3-glc as major pigments (Madhavi et al, 1995); in bilberry (V myrtillus) callus derived from hypocotyl, Cy 3-glycosides (gal, glc and ara) were produced, while fruit produced another 6 major components and 4 minor ones (Madhavi et al, 1998).…”
Section: Extraction Of Anthocyanins and Other Flavonoidsmentioning
confidence: 99%
“…Anthocyanin production was reported for the cultured cells of grape (Yamakawa et al, 1983, Do & Cormier, 1991, blueberry (Nawa et al, 1993), cranberry (Vaccinium macrocarpon Ait) (Madhavi et al, 1995), bilberry (Madhavi et al, 1998), strawberry (Asano et al, 2002) and Vaccinium pahalae (Meyer et al, 2002). Koda et al reported formation of blue pigment by Clerodendron trichotomum callus (1992), and formation of red pigment by perilla and their utilization as food colors (1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation